PENGARUH PRENATAL MASSAGE TERHADAP PENURUNAN NYERI PUNGGUNG PADA IBU HAMIL TRIMESTER III DI KLINIK ERNA KECAMATAN PADANG BOLAK KABUPATEN PADANG LAWAS UTARA - YENI ZAHARA HARAHAP (JURNAL ILMIAH MAKSITEK, 2019)
One complaint that is often experienced by third trimester pregnant women is that back pain is caused by the increased heavy burden carried by the mother, the baby in the womb (Walyani. 2015)The results of research conducted by Arum Sariati (2017) on "The Effect of Endorphin Massage on Reducing Back Pain of Trimester III Pregnant Women in the Health Center of Kabuh" shows that before the massage, almost half of the trimester III pregnant women experienced back pain on a scale of 4 (very painful ) as much as 45.7%, whereas after massage almost half of the third trimester pregnant women on a scale of 2 (slightly more painful) were 34.3%. According to Nofi Sukma Afika (2017).The hypothesis is a temporary answer to research, a standard of guessing, or a temporary proposition, the truth of which will be proven in the study (Notoatmojo, 2010). The hypotheses in this study are: H1 = There is an effect of Prenatal Massage on the reduction of back pain in third trimester pregnant women in the erna clinic, Padang district, North Padang regency.Based on the results of the study above, researchers can draw some conclusions as follows: 1. Decreased back pain in third trimester pregnant women before doing prenatal massage at erna clinic Padang sub-district, back in Padang Padang district, almost half of the third trimester pregnant women experience back pain with FPS-R slightly more pain. 2. Decreased back pain in third trimester mothers after prenatal massage in the erna clinic, Padang Bolak Subdistrict, Padang padang district, almost half of the third trimester pregnant women experience back pain with FPS-R with little pain. 3. There is an effect of prenatal massage on the reduction of back pain in third trimester pregnant women in the erna clinic, Padang Bolak District, Padang Utara District.